Cold spray technology: future of coating deposition processes - Harminder Singh; T.S. Sidhu; S.B.S. Kalsi (Fracture and Structural Integrity)
Cold spray (CS) belongs to a wide family of thermal spray technology with the difference that it is a solid state process in which spray particles are deposited via supersonic velocity impact at a temperature much below the melting point of the spray material. This paper briefly describes the various aspects of this rapidly emerging technology, with almost all the important parameters which affect the deposition behavior along with advantages and limitations; applications and history of emergence of this process is also reviewed. Though this technology emerges three decades ago but still it could not establish itself as viable practical industrial technology. Hence, the efforts, along with funding from public/private sources are required to commercialize this coating process. It is expected that next decade will saw the growth of cold spray as a viable coating process around the globe.